ANALISIS PENDIDIKAN KARAKTER PADA FILM “AGAK LAEN” KARYA MUHADKLY ACHO 2024 - Ice Monica Simorangkir; Marlina A. Tambunan; Vita Riahni Saragih (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to explore the values of character education in shaping the awareness and understanding of the audience that is relevant to their lives. This type of research is qualitative research with a content analysis approach. Data collection was carried out using document content analysis techniques in the form of text or content analysis. Then the data obtained was analyzed using data analysis techniques through several stages as follows: data reduction, data display, and conclusions. This research was conducted on the movie “Agak Laen”. The film “Agak Laen” was released in 2024 and premiered on February 1, directed by Muhadkly Acho.The results of this study conclude that this film not only functions as entertainment, but also as an effective medium in conveying character education values. These values are realized through the narrative and characters in the film, where the friendly relationship between the main characters reflects religious character and tolerance. Despite coming from different faith backgrounds, they show mutual respect and work together to solve problems, which illustrates the importance of appreciating diversity in society. Overall, the movie “Ag Agak Laen” succeeds in delivering character education messages in a light and fun way, making moral and character values acceptable without being patronizing. These messages are relevant and can serve as good examples for the audience of the importance of friendship, tolerance, hard work, creativity and responsibility in everyday life.